Multiply the numerator and denominator of the first question by 2 in order for both of the denominators to be the same.
1*2=2
3*2=6
Now that the denominators are the same, we can simply add the numerators and simplify if possible.
(2/6)+(1/6)= (3/6)
(3/6)= (1/2)
Final answer: 1/2
x^6 + 10ax^3 + 2ax^3 + 20a^2
(x^3 + 10a)(x^3 + 2a)
answer: (x^3 + 10a)(x^3 + 2a)
Hope it helps :)
Answer:
Approximately, the small pool will cost $16
Step-by-step explanation:
Answer:
(-3, 4)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtract Property of Equality
<u>Algebra I</u>
- Terms/Coefficients
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
y = -x + 1
2x + 3y = 6
<u>Step 2: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: 2x + 3(-x + 1) = 6
- Distribute 3: 2x - 3x + 3 = 6
- Combine like terms: -x + 3 = 6
- Isolate <em>x</em> terms: -x = 3
- Isolate <em>x</em>: x = -3
<u>Step 3: Solve for </u><em><u>y</u></em>
- Define equation: y = -x + 1
- Substitute in <em>x</em>: y = -(-3) + 1
- Simplify: y = 3 + 1
- Add: y = 4